2003
DOI: 10.1002/macp.200350010
|View full text |Cite
|
Sign up to set email alerts
|

Novel Polymerization of Fluorinated 2‐Vinylcyclopropane in Aqueous Solution via Cyclodextrin Complexes

Abstract: We report on the first examples of the free radical polymerization of a fluorinated 2‐vinylcyclopropane 1 and its copolymerization with an alkyl 2‐vinylcyclopropane 2 in aqueous solution via their host‐guest complexation with a random methylated β‐cyclodextrin (RAMEB) using a water‐soluble initiator (VA50). Upon polymerization, the dethreaded cyclodextrin remained in water solution, whereas the water‐insoluble polymer precipitated out and was isolated. The polymers prepared exhibited mesophase behavior over a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Our group has investigated the radical polymerization of several CD-complexed vinylmonomers. [10][11][12][13][14][15][16][17] It was shown that this new type of precipitating polymerization can be described by kinetic equations similar to those for classical polymerization in solution. [18,19] Furthermore, we have demonstrated that the polymerization of MMA-CD-complexes in aqueous medium using ATRP has a living character.…”
Section: Introductionmentioning
confidence: 99%
“…Our group has investigated the radical polymerization of several CD-complexed vinylmonomers. [10][11][12][13][14][15][16][17] It was shown that this new type of precipitating polymerization can be described by kinetic equations similar to those for classical polymerization in solution. [18,19] Furthermore, we have demonstrated that the polymerization of MMA-CD-complexes in aqueous medium using ATRP has a living character.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the preparation and polymerization of equimolar cyclodextrin complexes of commercial standard monomers like styrene 1 and methyl methacrylate (MMA have been described. It was also shown that the precipitation polymerization of a cyclodextrin complex of a poorly water-soluble monomer like MMA can be described by kinetic equations similar to those for the classical polymerization in solution [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The free-radical [5][6][7][8][9][10][11][12][13][14][15] and controlled 'living' [16] polymerizations of various CD-complexed vinyl derivatives and also some other types of monomers in water have recently been investigated. The synthesis of electrical conducting polymers from aqueous media via oxidative coupling have also been described, [17,18] and some kinetics of the homoand copolymerization of several kinds of CD-complexed monomers in aqueous medium have been studied.…”
Section: Introductionmentioning
confidence: 99%